Determination of Sugarcane Bagasse Fiber Reinforced Low Density Polyethylene Composites - Dalia Saber; Mohamed A. El-Meniawy; Ayman M. Abdelhaleim; Asmaa H. Abdelnaby; Kh. Abd El-Aziz (Current Approaches in Engineering Research and Technology Vol. 2, 2024)
The purpose of this research highlights about cellulose and cellulignin fibres obtained from sugarcane bagasse (SCB) waste can be used as reinforcing filler in a thermoplastic polymer matrix. Natural fiber composites are one of the most appealing replacements for non-biodegradable glass and carbon fibers in the fabrication of thermosetting and thermoplastic composites. In the recent decade, there has been an increase in global warming, environmental changes, and other issues. Environmentally friendly products, such as natural composite materials, are being developed by researchers and academics to protect life on the planet. The injection method was used to create the low-density polyethylene (LDPE) and sugarcane bagasse (SCB) composites. Fiber loading was set to be varied from 10 to 30 wt%. To improve interfacial bonding, the fibres were chemically modified using an alkali treatment, and the effects on the fiber/matrix interaction were evaluated using scanning electron micrographs (SEM). Tensile, impact, and hardness were used to determine the mechanical properties and corrosion tests. The study found that sugarcane bagasse fibers, like other natural fibers, reinforce polyethylene. The treated SCB fibers’ tensile strength and modulus were found to be greatly increased by around 13% and 196%, respectively, when compared to plain LDPE. This was owing to the observed improvement in interfacial adhesion between the fiber and matrix. The impact resistance and hardness of the composite enhanced by 55.28% and 26%, respectively, over neat LDPE. According to SEM analysis, the alkali treatment affected the morphology of fibers.